Sistem Pengendalian Operasional Kegiatan Dinas PU Bina Marga dan Cipta Karya Provinsi Jawa Tengah - Cahyono, Yudi; Cholil, Saifur Rohman; ., Khoirudin (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The Department of Public Works (PU) Bina Marga and Cipta Karya is a government agency responsible for supervising, planning and implementing the construction, maintenance and development of land transportation and housing infrastructure in the Central Java Province region. Currently, the Central Java Province Department of Public Works for Highways and Human Settlements has not utilized a web-based system to support the management of Activity Operational Control (POK). POK reporting that is still done manually will require a long time and process which will result in errors and delays in reporting. So, having a web-based computerized system can speed up the reporting process and management of POK. The Rapid Application Development (RAD) method is used to develop the POK System. The tools used are Unified Modeling Language (UML) as a means of designing POK systems. and The research results show that the use of RAD allows faster system development compared to other methods. Overall, the system that has been developed can increase ease of use and support acceleration in managing POK.